2007
DOI: 10.1136/thx.2006.076851
|View full text |Cite
|
Sign up to set email alerts
|

Long-term associations of outdoor air pollution with mortality in Great Britain

Abstract: Background: Recent studies have indicated long-term effects on mortality of particulate and sulphur dioxide (SO 2 ) pollution, but uncertainties remain over the size of any effects, potential latency and generalisability. Methods: A small area study was performed across electoral wards in Great Britain of mean annual black smoke (BS) and SO 2 concentrations (from 1966) and subsequent all-cause and cause-specific mortality using random effect models within a Bayesian framework adjusted for social deprivation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
78
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 45 publications
9
78
2
Order By: Relevance
“…Elsewhere, population studies in Norway (13), Japan (18), New Zealand (17), and China (38) have all reported statistically significant, positive associations with respiratory mortality. In the United Kingdom, a national ecologic study (39) reported larger effects of black smoke (a reflectance measure of black carbon particles ,4 mm in diameter) on respiratory mortality (HR, 1.19) in the most recent exposure periods (1990-1994), whereas a Scottish study (40) also found larger relationships with respiratory mortality (HR, 1.26). Our scaled findings for PM 10 and PM 2.5 (HR, 1.30 and 1.54, respectively, per 10 mg/m 3 ) adjusted for area income deprivation exceed all but one (38) of the reported estimates in Table 5; however, we note the smaller mean and standard deviation of our modeled concentrations compared with other studies.…”
Section: Discussionmentioning
confidence: 87%
“…Elsewhere, population studies in Norway (13), Japan (18), New Zealand (17), and China (38) have all reported statistically significant, positive associations with respiratory mortality. In the United Kingdom, a national ecologic study (39) reported larger effects of black smoke (a reflectance measure of black carbon particles ,4 mm in diameter) on respiratory mortality (HR, 1.19) in the most recent exposure periods (1990-1994), whereas a Scottish study (40) also found larger relationships with respiratory mortality (HR, 1.26). Our scaled findings for PM 10 and PM 2.5 (HR, 1.30 and 1.54, respectively, per 10 mg/m 3 ) adjusted for area income deprivation exceed all but one (38) of the reported estimates in Table 5; however, we note the smaller mean and standard deviation of our modeled concentrations compared with other studies.…”
Section: Discussionmentioning
confidence: 87%
“…Most long-term studies haven't reported elevated risks (9,15,18,37) with all-cause mortality. Positive effects have been observed in a study in Great Britain (39), in a recent reanalysis of the American Cancer Society cohort (40), and in many short-term studies with cardiovascular deaths and/ or hospital admissions (41).…”
Section: Discussionmentioning
confidence: 94%
“…Significant associations were found between black smoke (BS) and SO 2 concentrations and mortality. The effects were stronger for respiratory illness than other causes of mortality for the most recent exposure periods (shorter latency times) and most recent mortality period (lower pollutant concentrations) [30]. Air pollution has long-term effects on mortality and point to continuing public health risks.…”
Section: Relation Between Air Pollution and Mortalitymentioning
confidence: 96%
“…Air pollution has long-term effects on mortality and point to continuing public health risks. They therefore have importance for policies on public health protection through regulation and control of air pollution [30].…”
Section: Relation Between Air Pollution and Mortalitymentioning
confidence: 99%